EXPLORING THE HEALTH IMPACT OF CHEMICAL INDICATORS IN AMARANTH PRODUCTS - Mohidil Abduvalieva; Dilyora Khomidova; Dilshod Shodiev (Journal Park Publishing, 2024)
The cultivation of amaranth in Uzbekistan presents a promising opportunity for its widespread application across various sectors, including agriculture, medicine, and environmental management. This resilient plant plays a vital role in addressing contemporary challenges such as soil degradation and energy shortages. Amaranth thrives in saline soils with NaCl concentrations up to 10 mM, yielding high outputs even in such adverse conditions. Remarkably, after 2-3 years of growth in saline environments, the soil becomes suitable for wheat cultivation. Additionally, amaranth withstands high temperatures of 45-50°C, promoting the activity of nitrogen-fixing microorganisms and enhancing soil quality. Its robust root system improves soil porosity and contributes to humus restoration, making it an affordable and efficient green manure. Furthermore, as a phytoremediator, amaranth aids in the detoxification of soils by removing heavy metals, radionuclides, and pesticides. This versatile plant offers a sustainable solution to ecological and agricultural challenges in Uzbekistan.
Keywords: amaranth, chemical, vitamin, amaranth oil, malofene, squalene, protein, vitamins, biologically active substances, diseases.